PENGGUNAAN MODUL EDUKASI TENTANG PENINGKATAN PRODUKSI ASI MELALUI PEMBERIAN DAUN LEMBAYUNG DI PUSKESMAS SAIGON PONTIANAK - Dessy Hidayati Fajrin (JURNAL PARADIGMA (PEMBERDAYAAN & PENGABDIAN KEPADA MASYARAKAT), 2023)
The best nutrition in quality and quantity during the brain growth period which occurs from 0 months to 6 months is contained in exclusive breast milk. Coverage of babies receiving exclusive breastfeeding in Pontiaanak reached 60.3% of the 2100 babies aged 0-6 months in 2020. Saigon is a sub-district that has exclusive breastfeeding coverage which is still low, namely 76 (60%) of the 124 babies aged 0-6 months in the area. in the Saigon Pontianak Health Center Working Area, so improvements need to be made to improve this. Lembayung leaves are useful for stimulating the hormones oxytocin and prolactin such as alkoloids, saponins, polyphenols, steroids and flavonoids so that they can increase breast milk production.